Do Ecological or Molecular Biological Citizen Science Projects Affect the Perceptions of Undergraduate Students Toward Pursuing Future Citizen Science?. (1st December 2021) - Bedell, Kristin; Gates, Terry
Science literacy, including intrinsic motivation to participate in science outside of STEM careers, is an important goal of introductory biology courses aimed at non-majors. Citizen science may be able to support science literacy and science participation goals in such classes by providing authentic research opportunities matched to course content such as ecology or molecular biology. As yet, it is not known whether using citizen science of different biological disciplines in introductory biology courses for non-majors effectively increases undergraduates' motivation to participate in future citizen science. To investigate how the content focus of citizen science projects impacts students' attitudes toward future citizen science participation, we conducted a multilevel cross-classified analysis (mixed linear model) on four years of non-major biology students' student survey data (n = 2, 962) responding to ecological versus molecular biology citizen science project assignments using self-determination theory (SDT) as a backbone. Results suggest that general content categories of citizen science projects seem to be less influential on student attitudes toward future citizen science participation than are student-level characteristics and features of individual projects that promote competence and relatedness. Course instructors should be aware that adding citizen science projects simply for course content alignment is insufficient for promoting students' intrinsic motivation. Instead, time needs to be allotted for making deeper connections between the students and the projects.